Determinants of Cat Choice and Outcomes for Adult Cats and Kittens Adopted from an Australian Animal Shelter - Zito, Sarah (Animals (Basel), 2015)
SIMPLE SUMMARY: Commonly, more adult cats than kittens are euthanized in animal shelters. We surveyed 382 cat adopters to assess adoption outcomes and potential determinants of adopters’ choice of cat age group and price. Most adopters had benevolent motivations for adopting from the shelter and had put considerable thought into the adoption and responsible ownership requirements. However, adult cat adopters were more likely to have been influenced by price than kitten adopters. Adoption outcomes were generally positive in all age and adoption price groups. This study provides evidence to inform the design of strategies to encourage adult cat adoptions. ABSTRACT: The percentage of adult cats euthanized in animal shelters is greater than that of kittens because adult cats are less likely to be adopted. This study aimed to provide evidence to inform the design of strategies to encourage adult cat adoptions. One such strategy is to discount adoption prices, but there are concerns that this may result in poor adoption outcomes. We surveyed 382 cat adopters at the time of adoption, to assess potential determinants of adopters’ cat age group choice (adult or kitten) and, for adult cat adopters, the price they are willing to pay. The same respondents were surveyed again 6–12 months after the adoption to compare outcomes between cat age groups and between adult cats in two price categories. Most adopters had benevolent motivations for adopting from the shelter and had put considerable thought into the adoption and requirements for responsible ownership. However, adult cat adopters were more likely to have been influenced by price than kitten adopters. Adoption outcomes were generally positive for both adult cats and kittens and for adult cats adopted at low prices. The latter finding alleviates concerns about the outcomes of “low-cost” adoptions in populations, such as the study population, and lends support for the use of “low-cost” adoptions as an option for attempting to increase adoption rates. In addition, the results provide information that can be used to inform future campaigns aimed at increasing the number of adult cat adoptions, particularly in devising marketing strategies for adult cats.